Pattern of Utilization of Public Open Space in the Gorontalo Simpang Lima Roundabout Area - Faridah; Edward Syarif; Nurul Nadjmi (Departement of Architecture, Universitas Islam Indonesia, 2023)
Gorontalo City is a developing city, has several public spaces to support all community activities, such as city parks, street corners, markets, terminals and buildings. As one of the efforts to provide public open space, the Simpang Lima Roundabout Area was built which has a positive impact on the development of regional and surrounding activities, the existence of this area is experiencing congestion caused by several factors, such as traffic density, the emergence of formal activities. The purpose of this study was to determine the pattern of utilization of public open space at the Simpang Lima Roundabout. This study uses a positivistic paradigm with a descriptive qualitative approach supported by survey methods. The results showed that this pattern of open space utilization occurred in a circular or radial manner and linearly followed the circulation path, the use of open space at the intersection of five detected was shopping, meeting and chatting.Keywords: Public Open Space; Simpang Lima; Utilization Pattern